Mansour, Ahmad Ibrahim. “A Study in the Methodology of Economic Efficiency: ʿUmrān and Khaldūnian Reason as a Model,” Year 13, Issue 51 (Winter 1429 AH/ 2008 CE), Pp. 263 -284. - منصور, أحمد إبراهيم (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2008)
Ahmad Mansour’s article addresses ʿumrān (human civilizational development) in the thought of Ibn Khaldūn in light of taskhīr (utilization of natural resources), work, and preoccupation with human surroundings, and with what taskhīr has provided of resources for humans (human resources), whose creative energies are utilized in thought and action to create tools that help humans in harnessing natural resources and its laws. The article discusses the following themes: reason in the thought of Ibn Khaldūn, sources of knowledge according to Ibn Khaldūn, his position vis-a-vis reason and philosophy, preoccupation with surroundings (existence), and the features that emerge in both Bedouin and urban settings. The conclusion presents the impact of rational Islamic methodology in formulating an economic methodology.